Community Archaeology at Tel Esur - Bar, Shay (Biblical archaeology review, 2022)
The article offers the information that Tel Esur is located about 20 miles south of Haifa, at the western entrance to the narrow Nahal ‘Iron valley. It also discusses that The Tel Esur project, which began to remember the legacy of the late Yitzhak Dori, an Israeli educator and teacher from Metzer, who believed that educa- tion could be used to promote peace and friendship among people of all faiths and cultures.